Developments in Ophthalmology 2007
DOI: 10.1159/000098504
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor and the Potential Therapeutic Use of Pegaptanib (Macugen®) in Diabetic Retinopathy

Abstract: Both clinical and preclinical findings have implicated vascular endothelial growth factor (VEGF) in the pathophysiology of diabetic macular edema (DME). VEGF is both a potent enhancer of vascular permeability and a key inducer of angiogenesis. VEGF levels are elevated in the eyes of patients with DME, and in animal models of diabetes this elevation coincides with the breakdown of the blood-retinal barrier. Moreover, injection of VEGF (the VEGF165 isoform in particular) into healthy eyes of animals can induce d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 111 publications
0
34
0
7
Order By: Relevance
“…In fact, it was shown that injection of VEGF into healthy eyes of animals can induce diabetes-associated ocular diseases. 51 Notwithstanding, the involvement of other mechanisms, particularly stress proteins such as heat shock proteins, which have been implicated in IPC and are crucial to the survival of retinal ganglion cells, cannot be excluded. 52 Both IPC and postconditioning are highly effective strategies to protect the retina from an acute and deleterious ischemic episode.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it was shown that injection of VEGF into healthy eyes of animals can induce diabetes-associated ocular diseases. 51 Notwithstanding, the involvement of other mechanisms, particularly stress proteins such as heat shock proteins, which have been implicated in IPC and are crucial to the survival of retinal ganglion cells, cannot be excluded. 52 Both IPC and postconditioning are highly effective strategies to protect the retina from an acute and deleterious ischemic episode.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in diabetic animal models have shown that retinal vascular alterations resembling background diabetic retinopathy are associated with increases in retinal VEGF levels and increased expression of VEGFR2 (Gilbert et al, 1998;Hammes et al, 1998). Furthermore, blocking VEGF function can prevent diabetes-induced permeability increases in both patients (Avery et al, 2006;Haritoglou et al, 2006;Jorge et al, 2006;Starita et al, 2007) and animal models (Ideno et al, 2007;Ishida et al, 2003;Qaum et al, 2001), implying a direct role for VEGF in this pathology.…”
Section: Vegf and Diabetic Retinopathymentioning
confidence: 99%
“…Studies with a variety of VEGF blocking strategies have demonstrated the role of VEGF in the permeability response of diabetic animals (Ideno et al, 2007;Ishida et al, 2003;Qaum et al, 2001). Clinical trials in patients with diabetic macular edema have shown beneficial effects of anti-VEGF agents in reducing retinal vascular permeability as assessed by fluorescein angiography and decreasing macular edema as shown by optical coherence tomography (Avery et al, 2006;Haritoglou et al, 2006;Jorge et al, 2006;Starita et al, 2007). Recent data indicate that intravitreal injections of PEDF can also reduce vascular hyper-permeability in diabetic rats by a process associated with decreased levels of a variety of inflammatory mediators, including VEGF, VEGFR-2, MCP-1, TNF-α and ICAM-1 (Zhang et al, 2006a(Zhang et al, , 2006b).…”
Section: Vegf and Vascularmentioning
confidence: 99%
“…The emerging new therapies based on application of anti VEGF gave promising results in treatment of proliferative diabetic retinopathy (Adamis et al,. 2006;Starita et al, 2007;. Hernández-DaMota et al, 2010;Engelbert et al, 2011).…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%